Prematurity Affects Age of Presentation of Pyloric Stenosis. (February 2017) - Costanzo, Caitlyn M.; Vinocur, Charles; Berman, Loren
Term infants with hypertrophic pyloric stenosis (HPS) typically present between 4 and 6 weeks. There is limited consensus, however, regarding age of presentation of premature infants. We aim to determine if there is an association between the degree of prematurity and chronological age of presentation of HPS. A total of 2988 infants who had undergone a pyloromyotomy for HPS were identified from the 2012 and 2013 NSQIP-P Participant Use Files. Two hundred seventeen infants (7.3%) were born prematurely. A greater degree of prematurity was associated with an older chronological age of presentation ( P < .0001). Prematurity was significantly associated with an increase in overall postoperative morbidity, reintubation, readmission, and postoperative length of stay. When clinicians evaluate an infant with nonbilious emesis with a history of prematurity, they should consider pyloric stenosis if the calculated postconceptional age is between 44 and 50 weeks. When counseling families of premature infants, surgeons should discuss the increased incidence of postpyloromyotomy morbidity.